Withdrawn: Knowledge of Dentistry Students about Local Anesthetic Systemic Toxicity and Intravenous Lipid Rescue Therapy: A Cross-Sectional Questionnaire-Based Study (vol 26, pg 72-75, 2020) - Kaya Uğur, Berna (European Journal of Therapeutics, 2021)
DOI: 10.5152/eurjther.2021.112 Due to an administrative error, a duplicate of the manuscript [Kaya Uğur B. Knowledge of Dentistry Students about Local Anesthetic Systemic Toxicity and Intravenous Lipid Rescue Therapy: A Cross-Sectional Questionnaire-Based Study. Eur J Ther 2020; 26(1): 72-5.] was inadvertently published under the DOI [Kaya Uğur B. Knowledge of Dentistry Students on Local Anesthetic Systemic Toxicity and Intravenous Lipid Rescue Therapy: A Cross-Sectional Questionnaire-Based Study. Eur J Ther 2020; 26(4): 312-6.]. This duplicate manu-script has now been withdrawn. https://eurjther.com/index.php/home/article/view/388 https://eurjther.com/index.php/home/article/view/302